The critical thinking skills on global warming issue: Effect of the socio-scientific problems approach on problem-solving toward student’s - Rizqi Yanuar Pauzi; Sistiana Windiaryani (Universitas Negeri Jakarta, 2021)
This study aims to investigate the effect of socio-scientific issues learning approaches on problem-solving learning model toward improving the critical thinking skills of Islamic junior high public school students on global warming issue. The method used in this research was a quasi-experimental with a nonequivalent control group design. This study was conducted at one of the Islamic junior high public schools in Sukabumi with a research sample of class VII C as the experimental group and class VII B as the control. The sampling technique used was purposive. The instrument used was a test of critical thinking skills in the form of essays with as many as 9 items and questionnaires to investigate the response of students toward learning through 10 statements. The result of the research showed the average value of the experimental class N-gain of 0.38, which is higher than the control class of 0.24. Test of the difference in average critical thinking skills in the experimental class and control class using the t-test of N-gain data showed t-count 3.800> 2.009 t-table, therefore t-count> t-table, then H0 rejected and H1 accepted. So it can be concluded that the socioscientific issues learning approach affect the ability of student's critical thinking on global warming issue. Based on these results, we suggest that the socio-scientific issues learning approach can be applied by teachers in school for teaching with other socio-scientific issues such as genetic, ecology, and biodiversity.